The Empathy Paradox: Can AI Truly Replace the Human Element in Modern Medicine? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The integration of Artificial Intelligence AI into healthcare is rapidly transforming the landscape of medicine, promising breakthroughs in diagnostics, pers...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care